THE EXPERIENCES AND COPING STRATEGIES AMONG PRIMARY CARE GIVERS OF PLHIV - Shwetha Thorat (Indian Journal of Psychiatric Nursing)
HIV infection is a global pandemic that continues to escalate in a number of countries worldwide. United Nations and World health organization reported that the global figure of people living with PLHIV ranges between 30.6 and 36.1 million in the year 2007. The present study was conducted to assess the level of experiences and coping strategies among primary care givers of PLHIV. A descriptive research design was adopted to assess the level of experiences and coping strategies among primary caregivers of PLHIV. About 60 primary caregivers of PLHIV were selected from District Hospital Chitradurga. The convenient sampling method was used to select the subjects. The result revealed that most of the primary care givers of PLHIV had no unusual experiences (76.67%) and good coping strategies (70 %) while caring for the PLHIV.